2019
DOI: 10.3390/su11164475
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Opinions on the Use of Personal Learning Environments for Intercultural Competence

Abstract: Background: The aim of the present study was to evaluate teachers’ opinions on the use of Personal Learning Environments (PLE) for the development of students’ intercultural competences. Methods: This investigation carried out a thematic analysis of semi-structured interviews applied to a sample of n = 100 Compulsory Secondary Education teachers in Andalusia (Spain) with an average teaching experience of 13.13 years (SD = 6.63). The interview shows excellent content validity (Content Validity Index for the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
(100 reference statements)
0
11
0
3
Order By: Relevance
“…Finally, [26] indicated that the vast majority of secondary school teachers in Cádiz and Murcia state that they almost never engage in intercultural work outside the school. At this point, it is evident that in the initial and in-service teacher training there are gaps in relation to the attention to the cultural diversity of the students [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, [26] indicated that the vast majority of secondary school teachers in Cádiz and Murcia state that they almost never engage in intercultural work outside the school. At this point, it is evident that in the initial and in-service teacher training there are gaps in relation to the attention to the cultural diversity of the students [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…As with the strategies and reflection tools, the multimedia resources to mobile technologies in the relationship processes prevail, an important aspect to take into account in the training of future digital citizens, due to the rise of globalized, multicultural, digital and smart cities [63,134]. This leads one to consider that the role of the teacher to ensure the proper use of these resources will be fundamental [135], since, for example, tools like social networks can improve the intercultural relations of the students, but it can also be a means of segregation between them [66,136,137].…”
Section: Discussionmentioning
confidence: 99%
“…The social dimension of the PLE alludes to spaces of construction and collective interaction on knowledge, which are developed in a learning community, being understood as a group of people who share motivations and interests for some topic [13][14][15][16]. Learning communities also linked to the development and construction of intercultural interactions [60][61][62][63].…”
Section: Intercultural Learning Communitiesmentioning
confidence: 99%
“…More specifically, the authors concluded that through the use of determined PLE's, UFM improved their self-concept, planning and management of learning, use of educational strategies and tools, and social relationships within the educational setting. All of these are fundamental aspects of the social and academic integration of these students [36] and of the students who will form the basis of the present research. PLE's relate to the process through which students administer the information, resources and relationships they come across when engaging in learning [37,38].…”
Section: Introductionmentioning
confidence: 99%